Cover Image, Volume 234, Number 8, August 2019. Issue 8 (19th April 2019) - Diao, Yu; Yan, Weijie; Sun, Wei; Luo, Yanlin; Li, Junfa; Yin, Yanling
Abstract : Cover : The cover image is based on the Original Research Article The Dual Role of KCNQ/M Channels upon OGD or OGD/R Insults in Cultured Cortical Neurons of Mice: Timing is Crucial in Targeting M‐channels against Ischemic Injuries by Yu Diao et al., DOI: 10.1002/jcp.26990